Pelatihan uji kegunaan website menggunakan System Usability Scale (SUS) - Rahmat Novrianda Dasmen; Fatoni Fatoni; Alek Wijaya; Baibul Tujni; Sarita Nabila (Universitas Hamzanwadi, 2021)
System Usability Scale (SUS) is a usability testing technique for a simple system using a Likert scale. Testing and usability analysis assess user satisfaction with the system or web. So, the purpose of this service activity is to train website usability testing with SUS, using the Dukcapil website as a test object. Dukcapil's website will be analyzed for its usability level as a real case for direct practice. In SUS, ten statements are used as parameters in assessing the usability of a website. This activity was attended by 20 people, including Bina Darma University students, vocational students, and IT staff from the Dukcapil Palembang City. The usability analysis of this website aims to assess how well user interaction with the website is going. Then, the results of this assessment and study produce an input as a reference for website development to be more optimal in the future. In testing the usefulness of the Dukcapil website in this PKM activity, it can be seen that the SUS score is at a score of 56.125, with the category Acceptable. Therefore, it shows that the Dukcapil website is ranked F, with a